Analgesic effects of intraarticular anaesthetic lidocaine and methylprednisolone versus methylprednisolone alone following knee arthroscopy - Wahid Mohammed Hassan; Anas Amer Mohammad (International Association of Physical Chemists (IAPC), 2024)
Background: Knee arthroscopy is a widely practiced orthopaedic procedure known for its minimally invasive approach, allowing quicker recovery times and less postoperative discomfort than traditional open surgeries. However, managing postoperative pain remains a critical aspect of patient care and satisfaction. The main objective of this research is to examine the relationships between patient demographics (age, gender, BMI) and early postoperative outcomes, including pain, physiotherapy, and walking. Method: Randomized data collection, clinical trial study of 2 groups of patients. The patients were split into lidocaine 1 % 16 ml + methylprednisolone 160 mg 4 ml) and (methylprednisolone only 160 mg 4 ml) groups. All patients in both groups were queried about age, gender, BMI, and pain on the first, third, and 15th days following surgery. All patients were tested for physiotherapy on the second, third, and fourth postop days. After surgery, walking was tested on the third, fourth, and fifth days. Results: Significant differences in postoperative pain relief and physiotherapy initiation times were observed. There are notable associations between treatment groups and recovery metrics, such as pain levels and mobility on various days' post-surgery. Significant demographic influences (age, gender, BMI) on recovery outcomes are observed, particularly in walking and pain at day 15 post-operation. Conclusion: lidocaine and methylprednisolone improve postoperative pain relief and functional recovery in knee arthroscopy patients, with most experiencing reduced pain early post-surgery (early physiotherapy) and an expedited return to walking (decreased morbidity). Patients taking just methylprednisolone recovered slower. Age, gender, and BMI affected pain and walking abilities post-operation but not physiotherapy time, underscoring the personalised approach needed in postoperative treatment.